Necrotizing Infundibular Crystalline Folliculitis (NICF) Induced by Anti-Tumoral Therapies: Report of 2 Cases. (October 2017) - Fattouh, Kinda; Collet-Benzaquen, Diane; Provensal, Anne M.; Desseigne, Françoise; Castillo, Christine; Combemale, Patrick; de la Fouchardière, Arnaud
Abstract : Abstract: Necrotizing Infundibular Crystalline Folliculitis (NICF) is rare entity of unknown pathogenesis presenting as follicular crystalline papules arising in seborrheic areas. We report 2 cases of NICF in patients under targeted therapy for metastatic adenocarcinoma. In one case, the lesions reappeared cyclically every 3 weeks after each injection and in the other case, lesions persisted until disruption of the continuous oral therapy. Punch-biopsies demonstrated folliculitis with a plugging crystalline material associated with either bacteria or yeast. These are the first descriptions of drug-induced NICF.